Efektifitas Aromaterapi Lemon Dalam Mengurangi Mual Dan Muntah Pada Ibu Hamil Trimester 1 di TPMB D Gunung Putri Bogor Tahun 2025 - Emilia, Emilia; Oktavyani, Dian (STIKes Medistra Indonesia, 2025)
Nausea and vomiting in pregnancy are usually mild and are conditions that can be controlledaccording to the condition of the pregnant woman. This condition sometimes stops in the firsttrimester, but its effects can cause nutritional disorders, dehydration, weakness, weight loss, andelectrolyte imbalance. If left untreated, this nausea and vomiting will worsen to HyperemesisGravidarum. In handling nausea and vomiting during pregnancy, pharmacological and nonpharmacologicaltherapies can be used. One of the non-pharmacological therapies is to providelemon aromatherapy. Therefore, it is necessary to know the effectiveness of lemon aromatherapy inreducing nausea and vomiting in pregnant women in the first trimester at TPMB D Gunung PutriBogor in 2025. The design of this study used a quasi-experimental pre-post test one group. Thesampling technique was purposive sampling of 30 pregnant women in the first trimester. The resultsshowed a decrease in nausea and vomiting in pregnant women in the first trimester (p <0.05). Solemon aromatherapy is effective in reducing nausea and vomiting in pregnant women in the firsttrimester at TPMB D Gunung Putri Bogor in 2025